Symbolab como herramienta didáctica en el proceso de enseñanza-aprendizaje de la asignatura de matemática en los estudiantes de décimo año de educación general básica del paralelo “A” en la Unidad Educativa “Guaranda”, del cantón Guaranda, provincia Bolívar, durante el período lectivo 2022 –2023. - Tenelema Mesa, Manuel Agustín (2023)
This study sought to establish the measurement of the use of the Symbolab software in the learning of mathematics in the students of the Tenth Year of General Basic Education parallel "C, D, E and F", in the Educational Unit "Guaranda", located in Guaranda canton, Bolívar province. According to the established processes, those that were found in the academic activities in a virtual way because the institution was in the phase of repotentiation of its infrastructure, in this way the quantitative research approach of applied type with level scopes was used. explanatory and based on a quasi-experimental design. Students belonging to the Tenth Year EGB parallel "C, D, E and F" were taken, which added up to a virtual participation of 60 distributed in different class schedules and one teacher, the vast majority of whom attend a Basic Mathematics course, during the academic period 2022-2023. Following the non-probabilistic sampling, the 60 students of the mentioned educational unit were taken, being able to show that according to the interpretative analysis carried out, 50% of the students state that the teaching of mathematics, especially in the topics dealt with in those days the same as first degree equations and 2x2 equations, it is still done using the traditional method which with greater interest the following investigative work was carried out where the benefits of this educational software Symbolab were made known, the same one that showed incidence on the teaching-learning process